2019
DOI: 10.18433/jpps30444
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Multidrug Resistance-associated Protein 2 Activities by Knockdown of Phosphatidylinositol 4-phosphate 5-kinase in Hepatocytes and Cancer Cells

Abstract: Purpose: The plasma membrane localization and transport activity of multidrug resistance-associated protein 2 (MRP2/ABCC2) and P-glycoprotein (P-gp/ABCB1) efflux transporters are governed by transporter-associated proteins. Phosphatidylinositol 4,5-bisphosphate (PIP2) formed by phosphatidylinositol 4-phosphate 5-kinase type 1 (PIP5K1) activates the linker function of radixin for efflux transporters. Radixin is involved in the plasma membrane localization of efflux transporters. We examined whether PIP5K1 could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Many recent studies have shown that pre-treatment anemia is associated with poor survival in a variety of cancer patients. [ 31 , 32 ] However, the relationship between preoperative anemia and the prognosis of STS remains controversial. Our current results obtained from the meta-analysis of 12 studies including 2445 patients suggest that pre-treatment anemia is associated with the prognosis of STS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have shown that pre-treatment anemia is associated with poor survival in a variety of cancer patients. [ 31 , 32 ] However, the relationship between preoperative anemia and the prognosis of STS remains controversial. Our current results obtained from the meta-analysis of 12 studies including 2445 patients suggest that pre-treatment anemia is associated with the prognosis of STS.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have shown that pre-treatment anemia is associated with poor survival in a variety of cancer patients. [31,32] However, the relationship between preoperative anemia and the prognosis of STS remains controversial. Our current results…”
Section: Discussionmentioning
confidence: 99%